Geodesic flow on Finsler manifolds of hyperbolic type - HOUENOU, Djidémè Franck; OGOUYANDJOU, K.S. E. Carlos; TODJIHOUNDE, LEONARD (My University, 2020)
Let (X,F) be a compact Finsler (no reversibility is assumed) manifold and X ̃ be its Finsler universal covering. In this work we study the geodesic flow restricted to the set of all geodesics that are minimal on X ̃. In particular we give a comparison result between the topological entropy and the volume entropy of (X, F ).
Keywords: Finsler manifold; geodesic flow; topological entropy; volume growth